Restoration of Endodontically Treated Anterior Teeth by Modified Conservative Endocrowns: A Case Report with a 30-Month Follow Up - Kermanshah, Hamid; Altufaili, Maitham; Ghabraei , Sholeh; Sahib, Ali Muneer; Mahounak , Farzaneh Sadeghi (Journal of Dental School, 2021)
Objectives Restoration of severely damaged endodontically treated anterior teeth typically poses a challenge. Specific indication of post-retained restorations in such teeth has reasonably been questioned because of the potential tooth structure weakening. The present study aimed to describe a modified conservative endocrown (modified refers to intracanal extension while conservative refers to preparation at the finish line) to rehabilitate severely damaged anterior teeth. Case: Endodontically treated lower right central incisor had inadequate remaining tooth structure and restored by endocrwn restoration as a definitive treatment and followed for 30 month. Conclusion Considering the clinical outcome after 30 months of follow-up, it seems that this specific type of endocrown could efficiently serve as a conservative treatment approach to restore endodontically treated anterior teeth.